Writing history in the community of St Cuthbert, c.700-1130 : from Bede to Symeon of Durham - Rozier, Charles C. (Writing history in the Middle Ages, 2020)
An examination of the extraordinary texts produced by the community of St Cuthbert, showing how they were used to construct and define an identity.